Poscovid teachers’ perspectives about the use of technological instruments for teaching English at Mulaló Elementary School - Montesdeoca Aguaisa, Erick David (2022)
The challenges and opportunities of the new modality and of language teaching were very frequent points of discussion in the educational community. Appropriate strategies were needed to address and meet the needs of the learners. In other words, the proper handling of methodologies, and the different external factors in the teaching and learning process, required prior knowledge on the part of teachers. The teachers' and students' perspectives on the virtual modality and its effectiveness in the process of teaching and learning English were important points to discuss, as there were external and intangible difficulties in conducting the online classes, such as the psychological problems experienced by several of the students, as well as the teachers. Therefore, the main objective of this research is to explore the EFL teachers' perspectives on online education at Mulaló Elementary School. For the development of this project, the researchers used a qualitative method, considering semi-structured interviews using terms easily understood by the pre-service teachers. The results showed that the English teachers had to conduct prior research, as well as properly prepare themselves regarding the use of technological platforms and manage to carry out the teaching and learning process. Thus, the research results indicated that teachers were not familiar with the use of technological tools before the Covid 19 crisis and that they were not professionally prepared to carry out a fully virtual education, but they learned how to use them.